Multi-scalar and multi-modal wide-field imaging of artworks with a novel hyperspectral system - Ardini Benedetto; Corti Matteo; Candeo Alessia; Bassi Andrea; Cerullo Giulio; Valentini Gianluca; Comelli Daniela; Manzoni Cristian (EPJ Web of Conferences)
Hyperspectral imaging (HSI) is a very powerful tool to study artworks in a non-contact way. Nevertheless, typical HSI systems, which rely on spatial-scanning and dispersive spectrometers, suffer from high-light losses and are difficult to operate for analysing complex artworks. Here we review the capabilities of a HSI system based on TWINS, an innovative Fourier Tranform (FT) spectrometer, which allows wide-field imaging. We demonstrate how, by coupling the TWINS to different imaging systems, it is possible to achieve multi-scalar configurations from very large field-of-view (FOV) acquisition to microscopy. Further, we show how the high-collection throughput of the device allows for the sequential and fast detection of multi-modal signals’, as diffuse reflectance, transmittance, photoluminescence (PL) and Raman.